Potential use of dance game simulator in eye-leg coordination improvement: study on healthy participants - Wijaya, Ezra Bernardus; Boroh, Zeth; Baisa, Sahlah Yusuf; Arsyad, Noraeni (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND Game-based therapy has the potential to enhance patients’ participation in neurorehabilitation by making it more engaging and inspiring. Thus, this research aimed to investigate the efficacy and validity of a dance game simulator to improve eye-leg coordination diagnosis and treatment. METHODS 59 healthy participants aged 19–38 were assessed using a foot tapping test (FTT), lower extremity motor coordination test (LEMOCOT), modified agility ladder drill test, and total game score. The dance game system used 50, 100, and 150 beats per minute (bpm) songs to improve eye-leg coordination. The intervention group, consisting of 10 participants, received 15 sessions of 10-min play (3 songs each), while the control group, with 8 participants, had only 2 sessions: 1 at the start and 1 at the end. Rank correlation test compared game-based tests to validity, and t-tests analyzed pre- and post-game treatment results. RESULTS The validity of the LEMOCOT and the dance game with 100–150 bpm tempo in 59 healthy participants is showing correlation coefficients of r = 0.302 (right leg) and r = 0.305 (left leg), with p<0.01 for each leg. The dance game simulator improved FTT, left LEMOCOT, modified agility ladder drill test, and the overall dance game score after 15 sessions in the intervention group. However, these improvements were not statistically significant compared to the control group. CONCLUSIONS Game-based therapy offers an efficient alternative to traditional eye-leg coordination testing, providing a practical, clinically effective home rehabilitation method. Further research could enhance neurorehabilitation outcomes.